2009
DOI: 10.1007/s11013-009-9141-7
|View full text |Cite
|
Sign up to set email alerts
|

“Maybe I Made Up the Whole Thing”: Placebos and Patients’ Experiences in a Randomized Controlled Trial

Abstract: Patients in the placebo arms of randomized controlled trials (RCT) often experience positive changes from baseline. While multiple theories concerning such ''placebo effects'' exist, peculiarly, none has been informed by actual interviews of patients undergoing placebo treatment. Here, we report on a qualitative study (n = 27) embedded within a RCT (n = 262) in patients with irritable bowel syndrome. Besides identical placebo acupuncture treatment in the RCT, the qualitative study patients also received an add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
125
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(140 citation statements)
references
References 95 publications
12
125
0
3
Order By: Relevance
“…Generally the perception of the doctor can be analysed according to likeability and/or credibility (see [9,27,28]. These interviews further specify these findings by indicating that, at least in this study, the likeability of the doctor seemed to be the most important aspect.…”
Section: Do Accounts Of Patients' Direct Experiences Support This Expsupporting
confidence: 65%
“…Generally the perception of the doctor can be analysed according to likeability and/or credibility (see [9,27,28]. These interviews further specify these findings by indicating that, at least in this study, the likeability of the doctor seemed to be the most important aspect.…”
Section: Do Accounts Of Patients' Direct Experiences Support This Expsupporting
confidence: 65%
“…Alternatively, the focus was on 'generic' mechanisms rather than on those deemed to be specific to the trial intervention, in which case the message was less for the trial itself and more for a 'class' of intervention, such as 'self-management' 43 or 'placebo effects'. 41 Additionally, the research was sometimes designed to address a recognised body of theoretical work, such as theories of behavioural change. Researchers undertaking research in this subcategory reported a number of related reasons for doing so:…”
Section: Systematic Mapping Review Of Published Qualitative Research mentioning
confidence: 99%
“…expectancy, hope, conditioning, anxiety reduction.provides an inadequate model to explain its salubrious benefits.'' 16 Other recent research on the self-healing response both in CAM and conventional settings has similarly failed to clearly identify the patient factors which predispose to a strong self-healing response. 17,18,19 A number of the characteristics or patterns identified in the responder group are worthy of further investigation as possible predictors of response to this type of lifestyle intervention-whether the response being predicted is triggered by the treatment or by the self-healing effect.…”
Section: Discussionmentioning
confidence: 99%